Diafiltration flowrate is a determinant of the extent of adsorption of amikacin in renal replacement therapy using the ST150®-AN69 filter: An in vitro study. Issue 12 (December 2020) - Baud, Frédéric Joseph; Houzé, Pascal; Raphalen, Jean-Herlé; Winchenne, Anaïs; Philippe, Pascal; Carli, Pierre; Lamhaut, Lionel
Introduction: In continuous renal replacement therapy, conduction and convection are controlled allowing prescribing dosage regimen improving survival. In contrast, adsorption is an uncontrolled property altering drug disposition. Whether adsorption depends on flowrates is unknown. We hypothesized an in vitro model may provide information in conditions mimicking continuous renal replacement therapy in humans. Methods: ST150 ® -AN69 filter and Prismaflex dialyzer, Baxter-Gambro were used. Simulated blood flowrate was set at 200 mL/min. The flowrates in the filtration (continuous filtration), dialysis (continuous dialysis), and diafiltration (continuous diafiltration) were 1500, 2500, and 4000 mL/h, respectively. Routes of elimination were assessed using NeckEpur ® analysis. Results: The percentages of the total amount eliminated by continuous filtration, continuous dialysis, and continuous diafiltration were 82%, 86%, and 94%, respectively. Elimination by effluents and adsorption accounted for 42% ± 7% and 58% ± 5%, 57% ± 7% and 43% ± 6%, and 84% ± 6% and 16% ± 6% of amikacin elimination, respectively. There was a linear regression between flowrates and amikacin clearance: Y = 0.6 X ± 1.7 (R 2 = 0.9782). Conversely, there was a linear inverse correlation between the magnitude of amikacin adsorption and flowrate: Y = –16.9 X ± 84.1 (R 2 = 0.9976). Conclusion: Low flowrates resulted in predominant elimination by adsorption, accounting for 58% of the elimination of amikacin from the central compartment in the continuous filtration mode at 1500 mL/h of flowrate. Thereafter, the greater the flowrate, the lower the adsorption of amikacin in a linear manner. Flowrate is a major determinant of adsorption of amikacin. There was an about 17% decrease in the rate of adsorption per increase in the flowrate of 1 L/min.